Biliopancreatic diversion with duodenojejunal exclusion associated with truncal vagotomy: a new proposal for type 2 diabetes mellitus treatment - Alleotti,Edson (2012)
PURPOSE: To evaluate the effectiveness of the biliopancreatic diversion surgery with duodenojejunal exclusion in combination with truncal vagotomy in type 2 diabetes mellitus (T2DM) patients with overweight or class I or II obesity. METHODS: The study included ten patients with T2DM and class I or II obesity or overweight who were subjected to biliopancreatic diversion with duodenojejunal exclusion in combination with truncal vagotomy. The blood glucose levels during the pre- and postoperative periods were compared using the Friedman test. The significance level adopted was 5%. RESULTS: There were significant differences between preoperative and postoperative blood glucose levels at three months (p=0.01), six months (p=0.001) and 12 months (p=0.001). There was also a significant difference between one month postoperative blood glucose and six months postoperative blood glucose (p=0.01). Glycosylated hemoglobin levels decreased in 80% of patients, there was marked improvement in their lipid profiles, and the average BMI reduction was 7.0±1.5 kg/m² at 12 months after the surgery. CONCLUSION: In patients with type 2 diabetes mellitus associated with class I/II obesity or overweight, performing biliopancreatic diversion with duodenojejunal exclusion in combination with truncal vagotomy resulted in glycemic control, reduction of excess weight, and improvement of lipid profile 12 months after the surgery.